Optimization of ultra-sensitive humidity sensor from multi structured metal oxide-based semiconductor via hybrid deposition methods / N. E. A. Azhar … [et al.] - Azhar, N. E. A.; Eswar, K. A.; Maryam, M.; Malek, M. F.; Husairi, F. S.; Rusop, M. (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
The word humidity stands for the water vapor content in gases and are essential in everyday life where maintaining the suitable humidity level in the atmosphere improves health and quality of life. Significantly amid our COVID-19 pandemic, recent studies on the effects of temperature and humidity on the spread of COVID-19 had shown that one of the contributing factors in reducing the spread of COVID-19 virus is warm and wet climates hence the use of humidity sensor is required in detecting relative humidity (RH) level in the air. Commonly used sensing materials that are used in fabricating humidity sensors are metal oxide semiconductors particularly Titanium dioxide (TiO2) and zinc oxide (ZnO) nanomaterial due to their unique properties and boost excellent performances when applied to devices. Moreover, compared to organic materials substitution, metal oxides semiconductor not only has higher advantages in terms of producing higher quality humidity sensing device, but it can also be easily synthesized at much lower production cost. Therefore, our study will be focusing on the optimization of ultra-sensitive humidity sensor (USHS) from Multistructured Metal Oxidebased Semiconductor via various deposition techniques. An eco-friendly niobium-doped TiO2 and ZnO based metal-semiconductor-metal (MSM) humidity sensor has been fabricated and the high humidity sensor sensitivity had been investigated. Methods such as electrodeposition, spin-coating and microwave assisted ultrasonic techniques have been employed to synthesize the multi-structured metal oxides. Field emission scanning electron microscope (FESEM) images had shown uniformly distributed TiO2 and ZnO nanostructures with diameter ranging from 30 to 48.9 nm and length ranging between 0.4 to 1.82 µm. XRD results also had shown that these materials have high crystalline structures and the niobium doped TiO2 and ZnO based MSM humidity sensor showed the highest sensitivity of 258.63 at 90 %RH also exhibiting ultra-sensitive, high stability and faster response.